SARS-COV-2 Proteins, in Complex with Tirilazad - Ferrari, I.V.; Mario, M. Di (International Journal of Scientific Research in Computer Science and Engineering, 2022)
In this study, our approach was to carry out a complete investigation of molecular docking analysis with the major SARS-CoV-2 proteins. We analysed more than 6000 drugs, downloaded by the PubChem database. Particular attention, we have focused on Spike Glycoprotein and Main protease 3CLpro Covid-19 proteins, by “Blind docking” method and “Selective docking” procedure, in Ligand Binding site, with AutoDock Vina using Pyrx software. From our results, we have selected Tirilazad against COVID-19. In fact, it reported having an excellent ability to bind both with the “Native Spike Glycoprotein”, with a Binding Energy of -11.8 kcal mol-1, and with the South African (B.1.351) SARS-CoV-2 spike protein variant, with a Binding Energy -10 kcal mol-1. Indeed, in the second case, the docking analysis was evaluated in the active area of three key amino acids belonging to the Spike Protein RBD, responsible for a higher binding with the ACE2 receptor. They are ASN 417, Lys 484, and Tyr 501 respectively. In addition, Tirilazad has shown a Binding energy score of approximately -10.5 kcal mol-1 against SARS-COV-2 Main protease. This has led us to conclude that this drug could be an excellent candidate against Coronavirus (COVID-19) pandemic, even though further in vitro and in vivo studies are needed.